2010
DOI: 10.5194/acp-10-9705-2010
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radicals in the tropical troposphere over the Suriname rainforest: comparison of measurements with the box model MECCA

Abstract: As a major source region of the hydroxyl radical OH, the Tropics largely control the oxidation capacity of the atmosphere on a global scale. However, emissions of hydrocarbons from the tropical rainforest that react rapidly with OH can potentially deplete the amount of OH and thereby reduce the oxidation capacity. The airborne GABRIEL field campaign in equatorial South America (Suriname) in October 2005 investigated the influence of the tropical rainforest on the HO<sub>x</sub> budget (HO<sub>… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
118
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(135 citation statements)
references
References 72 publications
15
118
2
Order By: Relevance
“…Our results suggest that in the fresh plumes, the vertical transport predominates with the oxidative capacity reaching its maximum at 1,000 m. In the flight tracks classified as BG, we observed the widest variation in the average OH concentration using the new sequential reaction model (Figure 9, on bottom), especially in upper levels (0.5 -1  10 6 molecules cm -3 ), although reported a lower confidence level in this presented an increase near to CL (~1,000 m), in agreement with previous studies (Karl et al, 2007;Kuhn et al, 2007;Langford et al, 2005;Mauldin et al, 1997). Several studies investigated the uncertainties in the isoprene oxidation mechanism, and most of them focus on OH concentration levels through observational and modeling studies (de Gouw et al, 2006;Kubistin et al, 2010;Kuhn et al, 2007;Lelieveld et al, 2008;Lu et al, 2012;Whalley et al, 2014;Yokelson et al, 2007). Under a high isoprene and low-NO atmospheric regime, there is a controversial discussion about the impact on the oxidative capacity in forest sites.…”
Section: Oh Predicted Using Sequential Reaction Approachsupporting
confidence: 74%
“…Our results suggest that in the fresh plumes, the vertical transport predominates with the oxidative capacity reaching its maximum at 1,000 m. In the flight tracks classified as BG, we observed the widest variation in the average OH concentration using the new sequential reaction model (Figure 9, on bottom), especially in upper levels (0.5 -1  10 6 molecules cm -3 ), although reported a lower confidence level in this presented an increase near to CL (~1,000 m), in agreement with previous studies (Karl et al, 2007;Kuhn et al, 2007;Langford et al, 2005;Mauldin et al, 1997). Several studies investigated the uncertainties in the isoprene oxidation mechanism, and most of them focus on OH concentration levels through observational and modeling studies (de Gouw et al, 2006;Kubistin et al, 2010;Kuhn et al, 2007;Lelieveld et al, 2008;Lu et al, 2012;Whalley et al, 2014;Yokelson et al, 2007). Under a high isoprene and low-NO atmospheric regime, there is a controversial discussion about the impact on the oxidative capacity in forest sites.…”
Section: Oh Predicted Using Sequential Reaction Approachsupporting
confidence: 74%
“…Previous modelling studies of forested environments with high biogenic VOC emissions have significantly underestimated the observed OH concentrations (Tan et al, 2001;Kubistin et al, 2010;Hofzumahaus et al, 2009;Whalley et al, 2011;Stone et al, 2011). A simulation with unconstrained OH for OP3 exhibits a similar result (not shown but consistent with Whalley et al, 2011).…”
Section: Sensitivity To Oh Concentrationsupporting
confidence: 73%
“…This reaction imply that isoprene have no net impact on OH concentrations. This conclusion is drawn also by Kubistin et al (2010) 10 who found better agreement between simulated and measured HO x concentrations by ignoring the isoprene chemistry. As the chemistry of isoprene is not well understood, the results obtained in our work are subject to these uncertainties.…”
supporting
confidence: 61%